Measuring the factors that contribute to the quality of services in the restaurants in Republic of Macedonia (European Journal of Marketing and Economics, 2024)
This study examines contemporary consumer behavior within the restaurant industry of Macedonia, providing a rigorous, critical evaluation of current marketing practices and their direct impact on customer satisfaction. Beyond analyzing the perception gaps between restaurant employees and consumers regarding what drives dining decisions, this paper isolates the primary informational tools customers utilize to discover new restaurant offers and evaluates ten core operational and sensory factors, including food quality, taste, accessibility, food decoration, customer care, innovation, price, hygiene, ambience, and marketing promotion. The empirical findings paint a clear picture of the strategic opportunities and structural challenges facing Macedonian hospitality managers today by identifying precisely which operational variables generate the highest return on customer loyalty. Consequently, the study gives explicit directions for implementing advanced analytical techniques and modern marketing methods within the culinary sector. Ultimately, this research serves as a practical blueprint, offering targeted recommendations for developing tailored marketing strategies designed to maximize consumer satisfaction, optimize service quality, and drive long-term business growth in a highly competitive regional market.
Keywords: bringing decision, customer behavior, customer satisfaction, restaurant businesses